Criss Cross - Perkins, Lynne Rae. (New York : Greenwillow Books, 2005)
Teenagers in a small town in the 1960s experience new thoughts and feelings, question their identities, connect, and disconnect as they search for the meaning of life and love.
Keywords: Identity -- Fiction; Nineteen sixties -- Fiction